Implementation Occupational Health And Safety Management System At PT Kereta Api Indonesia-Cirebon - Hanifah Handayani (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
In today's human life full of mobility, transportation is indispensable every day. There are personal and mass means of transportation. One of the most popular means of mass transportation today is the train. This train consists of locomotives as propulsion engines and carriages used for passengers or goods. Because this train is a mass transportation, if there is an accident, it will cause very many casualties or large losses. Accidents have a negative impact, including at PT Kereta Api Indonesia, so the government issued Law No. 13 of 2003 concerning Manpower, Government Regulation No. 50 of 2012 concerning the application of safety management, Occupational Health (SMK3) and for railways there Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 69 of 2018. Research was conducted literature studies and qualitative methods. As a result, PT Kereta Api Indonesia-Cirebon (PT KAI-Cirebon) has implemented SMK3 in accordance with Government Regulation No. 50 of 2012 and gradually the procedures made were revised to the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 69 of 2018. From this research, it can be concluded that SMK3 at PT KAI-Cirebon has implemented SMK3, although it is not perfect and is still under revision, and the implementation of SMK3 PT KAI-Cirebon, which originally referred to PP no 50 of 2012, was gradually revised to the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 69 of 2018.